2017
DOI: 10.12797/moap.23.2017.38.03
|View full text |Cite
|
Sign up to set email alerts
|

Translation Theory From Students’ Perspective: an Indispensable Professional Prerequisite or a Tedious Curricular Obligation?

Abstract: The paper presents and analyses the outcomes of a survey study conducted with the participation of BA and MA students in a translation programme, aimed at gaining insight into the students’ views on translation theory usefulness. It was initially assumed that theory appreciation would develop along with growing translation experience, however, the nature of the predicted correlation appeared more complex. The author attempts to determine what factors may influence the observed interconnection and affect the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The only study that has touched upon students' and teachers' knowledge of theory is König (2018) who found that students and teachers favor theories that guide interpreting learning and practice, and that the two most popular theories are the Effort Models (EM) and Interpretive Theory of Translation (ITT). This is similar to a study of translation theory which found that students expect to learn theories that guide their translation practice in particular situations (Giczela-Pastwa, 2017).…”
Section: Current Evidence On Theory Teaching In Interpreter Trainingsupporting
confidence: 80%
See 3 more Smart Citations
“…The only study that has touched upon students' and teachers' knowledge of theory is König (2018) who found that students and teachers favor theories that guide interpreting learning and practice, and that the two most popular theories are the Effort Models (EM) and Interpretive Theory of Translation (ITT). This is similar to a study of translation theory which found that students expect to learn theories that guide their translation practice in particular situations (Giczela-Pastwa, 2017).…”
Section: Current Evidence On Theory Teaching In Interpreter Trainingsupporting
confidence: 80%
“…Agost and Ordóñez López (2015), Shih (2011) and Sung (2016) found that Spanish, British, and Korean translation students hold a positive attitude towards translation theory. By contrast, Jeong (2000), Li (2002), andGiczela-Pastwa (2017) found that translation students in Korea, Poland and Hong Kong held negative attitudes towards theory. Seung et al (2001) and Wali (2015) found that, while the role of theory is recognized by translation teachers, it is less considered so by students.…”
Section: Current Evidence On Theory Teaching In Interpreter Trainingmentioning
confidence: 99%
See 2 more Smart Citations